2017
DOI: 10.1503/jpn.160129
|View full text |Cite
|
Sign up to set email alerts
|

Decreased uncinate fasciculus tract integrity in male

Abstract: IntroductionApproximately 10% of trauma-exposed individuals have posttraumatic stress disorder (PTSD), 1 characterized by intrusions and avoidance of reminders of the traumatic event, altered cognitions and mood, and hyperarousal.2 The prevailing neurocircuitry model of PTSD postulates amygdala hyperactivity and ventromedial prefrontal cortex (vmPFC) hypoactivity.3,4 The amygdala plays a pivotal role in fear expression and salience processing, 5 whereas the vmPFC is important in top-down control over the fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 65 publications
4
22
0
Order By: Relevance
“…By pooling data across scanners, we further demonstrated the robustness of the predictive utility of uncinate fasciculus FA for longterm PTA with respect to both acquisition and processing method from the present sample. Several reports have found uncinate fasciculus microstructure to vary with traditional PTSD symptom clusters (Costanzo et al, 2016;Harnett, Ference et al, 2020;Koch et al, 2017;Olson et al, 2017;Santhanam et al, 2019), although to date only one prior study has investigated its role in PTA symptoms (Fani et al, 2019). Further, few studies have utilized a longitudinal design to identify whether white matter microstructure assessed acutely post-trauma is predictive of future PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By pooling data across scanners, we further demonstrated the robustness of the predictive utility of uncinate fasciculus FA for longterm PTA with respect to both acquisition and processing method from the present sample. Several reports have found uncinate fasciculus microstructure to vary with traditional PTSD symptom clusters (Costanzo et al, 2016;Harnett, Ference et al, 2020;Koch et al, 2017;Olson et al, 2017;Santhanam et al, 2019), although to date only one prior study has investigated its role in PTA symptoms (Fani et al, 2019). Further, few studies have utilized a longitudinal design to identify whether white matter microstructure assessed acutely post-trauma is predictive of future PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly Prior work has demonstrated that PTSD is associated with alterations in white matter pathways that interconnect neural circuitry critical for fear-and reward-related processes that are dysfunctional in PTSD (Fenster et al, 2018;Harnett, Goodman et al, 2020). Specifically, fractional anisotropy (FA) of the uncinate fasciculus (amygdala to ventromedial prefrontal cortex [PFC]) and cingulum bundle (PFC to posterior cingulate and hippocampus) is reduced in individuals with PTSD compared to non-PTSD controls (Costanzo et al, 2016;Fani et al, 2016;Koch et al, 2017;Olson et al, 2017;Sanjuan et al, 2013). In addition, the fornix (which connects the hippocampus to deep-brain nuclei), may also be involved in PTSD; prior research has demonstrated increased fornix and stria terminalis FA over time within treatment-resistant PTSD patients (Kennis et al, 2015) and fornix FA has been found to be positively related to trait anxiety (Modi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3 , the shape and trajectory of the UF are highly consistent with the template (Yeh, 2020 ) and previous literature (Maier-Hein et al, 2017 ; Park et al, 2019 ; Sanvito et al, 2020 ). The UF is the major white matter tract connecting the ventral pre-frontal cortex and the amygdala (Koch et al, 2017 ), which takes a crucial part of the bidirectional communication within the amygdala-vPFC circuit. However, it is unclear how the structural connectivity of the UF relates to amygdala related emotional impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies did not observe differences in the CAB, but instead showed WMT changes in uncinate fasciculus, a white matter tract connecting the AMY to the vmPFC, a decit possibly underlying reduced inhibitory control over the fear response. 78 Other investigators have taken a networking approach and reported distinct differences in the white matter tracts of the salience network between PTSD and control participants. 67,79 Overall, these studies are preliminary and few current literature reviews or metanalyses on this topic are available.…”
Section: Clinical Imaging Techniquesmentioning
confidence: 99%